FOXM1-Dependent Transcriptional Regulation of EZH2 Induces Proliferation and Progression in Prostate Cancer - Tian, Juan-Hua; Mu, Li-Jun; Wang, Mei-Yu; Zeng, Jin; Long, Qing-Zhi; Bin-Guan; Wang, Wen; Jiang, Yu-Mei; Bai, Xiao-Jing; Du, Yue-Feng (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Prostate cancer is one of the most commonly diagnosed cancers and one of the most common causes of cancer-related deaths among men worldwide. Patients who are diagnosed with localized prostate cancer and treated with radical prostatectomy often respond well to therapy. The current standard therapy for prostate cancer involves maximal surgical resection, followed by radiotherapy and chemotherapy. Clarifying the molecular mechanism of tumor proliferation and recurrence becomes more and more important for clinical therapies of prostate cancer. Methods: Quantitative Real-Time PCR and Western-blot were used in the detection of mRNA and protein expression. Lentivirus infection was used to overexpress or knockdown the target gene. Flow cytometry analysis was performed to test protein expression and apoptosis level. Immunohistochemistry was used to identify protein expression in tissue. Statistical differences between the two groups are evaluated by two-tailed t-tests. The comparison among multiple groups is performed by one-way Analysis of Variance (ANOVA) followed by Dunnett’s posttest. The statistical significance of the Kaplan-Meier survival plot is determined by log-rank analysis. Results: In this study, we identified that FOXM1 expression was significantly enriched in prostate cancer compared with normal tissue. Additionally, FOXM1 was functionally required for tumor proliferation and its expression was associated with poor prognosis in prostate cancer patients. Mechanically, FOXM1-dependent regulation of EZH2 is essential for proliferation and progression in prostate cancer. Conclusion: Taken together, our data suggest that oncogenic transcription factor FoxM1 is up-regulated in prostate cancer, suggesting that the growth of cancer cells may depend on FOXM1 activity. FOXM1 may serve as a clinical prognostic factor and a therapeutic target for prostate cancer.
Keywords: prostate cancer